PENGARUH PEMASARAN DIGITAL DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN ONLINE DENGAN PENGELOLAAN HUBUNGAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA PELANGGAN E-COMMERCE DI KOTA BANDA ACEH - Farhanurrizka Farhanurrizka; Mukhlis Yunus (Departemen Manajemen, 2023)
This study aims to examine the effect of digital marketing and trust on online purchasing decisions with customer relationship management as a mediating variable on e-commerce customers in Banda Aceh City. The population in this study are e-commerce customers in Banda Aceh City. The number of samples is determined with the condition that the minimum number of samples is for Structural Equation Modeling (SEM) analysis which uses a formula of 10 times the number of indicator variables, totaling 14 indicators used (Ferdinand,2013) which amounts to 140 samples. The results showed that 1) Online Purchase Decisions, Customer Relationship Management, Digital Marketing, and Trust in e-commerce Customers in Banda Aceh City were good. 2) Digital Marketing affects the Management of Customer Relations with e-commerce Customers in Banda Aceh City. 3) Trust has an effect on the management of customer relations with e-commerce customers in Banda Aceh City. 4) Digital Marketing has an effect on Online Purchase Decisions for e-commerce Customers in Banda Aceh City. 5) Trust has no effect on Online Purchase Decisions for e-commerce Customers in Banda Aceh City. 6) Customer Relationship Management has an effect on Online Purchase Decisions for e-commerce customers in Banda Aceh City. 7) Customer Relationship Management partially mediates the influence of Digital Marketing on Online Purchase Decisions of e-commerce Customers in Banda Aceh City. 8) Customer Relationship Management fully mediates the influence of Trust on Online Purchase Decisions on e-commerce customers in Banda Aceh City.